Addressing the Gap, Advancing the Knowledge: Guidance for the Abstract Reviewer. (29th September 2021) - Orozco, Gwendelyn S.; Barreras, Rudy R.; Hicks, Rodney W.
ABSTRACT: Conferences often offer a wide variety of informative podium, expert panel, and poster presentations. Conference planners use an abstract review process to select abstracts for the presentations. Although guidance exists for writing abstracts, much less information is available on reviewing abstracts and what constitutes an appropriate review. This article provides an overview of the role of an abstract reviewer and information that potential reviewers can use to improve the quality of their reviews. A competent reviewer should possess current knowledge of the profession and working knowledge of research methodology, data collection strategies, and analyses to assess an abstract. Abstract reviewers should consider the abstract in the context of the planned conference attendees, remain objective throughout the review process, and complete the review in a timely manner. Conference planners rely on objective reviews to ensure the selection of quality abstracts, which can lead to a successful conference that advances professional knowledge.